2007
DOI: 10.1104/pp.107.099838
|View full text |Cite
|
Sign up to set email alerts
|

A Study of Gibberellin Homeostasis and Cryptochrome-Mediated Blue Light Inhibition of Hypocotyl Elongation

Abstract: Cryptochromes mediate blue light-dependent photomorphogenic responses, such as inhibition of hypocotyl elongation. To investigate the underlying mechanism, we analyzed a genetic suppressor, scc7-D (suppressors of cry1cry2), which suppressed the long-hypocotyl phenotype of the cry1cry2 (cryptochrome1/cryptochrome2) mutant in a light-dependent but wavelength-independent manner. scc7-D is a gain-of-expression allele of the GA2ox8 gene encoding a gibberellin (GA)-inactivating enzyme, GA 2-oxidase. Although scc7-D … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
160
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 149 publications
(174 citation statements)
references
References 64 publications
14
160
0
Order By: Relevance
“…The main target of LONG1-dependent light regulation appears to be GA2ox2, consistent with the conclusions of Reid et al (2002), although smaller effects on other genes may also contribute. Induction of Arabidopsis GA2ox genes by light has also recently been reported (Achard et al, 2007;Zhao et al, 2007;AlabadĂ­ et al, 2008), and Arabidopsis GA2ox1 was also found to be HY5-regulated in transcript profiling studies (Sibout et al, 2006;Lee et al, 2007). These findings suggest that Arabidopsis HY5 may play a similar role in light regulation of the GA pathway, although this has yet to be directly tested.…”
Section: Long1 and Light Regulation Of Ga Biosynthesissupporting
confidence: 54%
“…The main target of LONG1-dependent light regulation appears to be GA2ox2, consistent with the conclusions of Reid et al (2002), although smaller effects on other genes may also contribute. Induction of Arabidopsis GA2ox genes by light has also recently been reported (Achard et al, 2007;Zhao et al, 2007;AlabadĂ­ et al, 2008), and Arabidopsis GA2ox1 was also found to be HY5-regulated in transcript profiling studies (Sibout et al, 2006;Lee et al, 2007). These findings suggest that Arabidopsis HY5 may play a similar role in light regulation of the GA pathway, although this has yet to be directly tested.…”
Section: Long1 and Light Regulation Of Ga Biosynthesissupporting
confidence: 54%
“…The GA 3 biosynthesis in low and high nitrate The endogenous GA levels are not constant level during different time points in wild type Arabidopsis in light/dark cycles (Hisamatsu et al 2005;Zhao et al 2007). It oscillates in a diurnal or in a clock-controlled manner (Figs 3a, c).…”
Section: Resultsmentioning
confidence: 97%
“…Under GAdeficient conditions, photomorphogenesis is partially de-repressed in the dark (Alabadi et al, 2004). In addition, blue light inhibits GA20ox1 and GA3ox1 expression whereas it increases GA2ox1 expression in de-etiolated seedling (Zhao et al, 2007). These changes in GA metabolism genes correlate with transient reduction in GA 4 levels.…”
Section: Light Regulation During Photomorphogenesismentioning
confidence: 96%